DNA analysis from human skeletal remains in forensic casework. (December 2017) - Zgonjanin, Dragana; Antov, Mirjana; Alghafri, Rashed; Petković, Stojan; Vuković, Radenko; Stojiljković, Goran; Toljić, Danka
Abstract: To assess our laboratory's success with skeletal remains and provide a benchmark for the forensic community involved in identification of these remains, we retrospectively examined our ability to develop DNA profiles from the remains analyzed in our laboratory in the last 7 years. Between January 2009 and December 2016, 70 DNA extractions were completed on skeletal remains from routine casework. 92% of skeletal remains analyzed were samples submitted for body identifications by law enforcement and only 8% were samples submitted to answer family identity or historical questions. Overall, the ability to obtain a full or partial profile primarily reflects the difference in the average age and the condition of the samples in these two categories and thus, difference in the quantity and quality of the DNA. We describe here the approximate age and type of remains we have received, whether a full, partial, or no profile was obtained, as well as the condition of the samples.